2018
DOI: 10.4995/wrs.2018.9823
|View full text |Cite
|
Sign up to set email alerts
|

Haematological response in the treatment of naturally acquired ectoparasite infestations in rabbits

Abstract: The objective of this study was to determine changes in haematological values of topical administration of selamectin in rabbits with at least one species of naturally acquired ectoparasite infestation (<em>Sarcoptes scabiei</em> var. <em>cuniculi</em>, <em>Psoroptes cuniculi</em>, or <em>Cheyletiella</em> spp). Thirty-five rabbits were enrolled. They underwent physical examination and assessment of ectoparasite infestations on days 0, 14, 28, 56 and 86. Blood fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These alterations were mainly attributed to the mite's toxic excretory products and its irritating effect. Logically, this hepatic damage took apart in the former hypoalbuminemia, as the liver is the major site of albumin formation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…These alterations were mainly attributed to the mite's toxic excretory products and its irritating effect. Logically, this hepatic damage took apart in the former hypoalbuminemia, as the liver is the major site of albumin formation (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Cheyletiella species, selamectin has been efficiently applied once at a dose of 12 mg/kg·b/wt [ 97 ] or at doses of 6.2–20.0 mg/kg·b/wt 1–3 times during an interval of 2–4 weeks [ 98 ]. Moonarmart et al [ 99 ] revealed that topical application of selamectin at a dose of 15 mg/kg·b/wt at a 2-week interval was effective and safe in the control of Sarcoptes scabiei var. cuniculi , Psoroptes cuniculi , and Cheyletiella species for at least 58 days after treatment.…”
Section: Control Strategiesmentioning
confidence: 99%
“…The complete blood cell count (CBC) is a routine, inexpensive, and easily requested laboratory test that allows evaluation of abnormalities in blood cells, their kinetic in the inflammatory process, and identification of hematologic disorders (Tefferi et al ., 2005; Stockham and Scott, 2011). Hematologic changes associated with hematophagous ectoparasites, such as mites (Szabó et al ., 2002; Moonarmart et al ., 2018), flies (O'Brien et al ., 2001), ticks (Pfäffle et al ., 2009; Reck et al ., 2009), mosquitoes (Jones and Lloyd, 1987), fleas (Araujo et al ., 1998), bed bugs, and kissing bugs (Pritchard and Hwang, 2009), have been reported for animals and people.…”
Section: Introductionmentioning
confidence: 99%